1996
DOI: 10.1021/la9605596
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a Tethered Chromophore Imbedded in a Self-Assembled Monolayer

Abstract: We report the first measurements on the dynamical response of alkanethiol/gold monolayers using a depth-selective tethered probe molecule technique, where 5% of the monolayer is comprised of the probe. Our transient spectroscopic data indicate that, for the first ∼10 CH2 groups above the gold surface, the local environment is highly rigid, and from these same data, we recover an average tilt angle of 26°, in exact agreement with steady state measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 32 publications
(49 reference statements)
0
38
0
Order By: Relevance
“…Alternatively, we can suggest that oxygen quenching of the pyrene singlet excited state on a solid surface is more effective than in the bulk solution. We also note that the surface-bound chromophore exhibits a non-exponential decay, characteristic of either multiple emitting species, efficient collisional quenching or Ffrster excitation transport [13]. It is clear that further experimentation will be required to distinguish between these several possibilities.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Alternatively, we can suggest that oxygen quenching of the pyrene singlet excited state on a solid surface is more effective than in the bulk solution. We also note that the surface-bound chromophore exhibits a non-exponential decay, characteristic of either multiple emitting species, efficient collisional quenching or Ffrster excitation transport [13]. It is clear that further experimentation will be required to distinguish between these several possibilities.…”
Section: Resultsmentioning
confidence: 93%
“…Pyrene is a well-known fluorescent probe that has been used widely to study local polarity in the solution phase. The spectral response of surface-bound pyrene is also useful for characterizing mono-and multilayer structures [12,13].…”
Section: Resultsmentioning
confidence: 99%
“…The most well-studied systems involve alkanethiols grown on Au surfaces [8,9,78,79,104,117,122], although sulphur also shows a strong affinity towards the other noble/ coinage metals, including Ag [9], Pt, Cu, Hg and Pd. Au is most often chosen due to its inertness and resilience to oxidation-so we shall start by discussing this system.…”
Section: Self Assembled Monolayersmentioning
confidence: 99%
“…Our strategy of tethering retinal to the surface by covalent chemistry is similar to other approaches aimed at chromophore surface localization [11]. Such studies have shown that covalent attachment via specific functional groups minimizes the translational freedom within the monolayer only to the rotational motion intrinsic to the molecules directly attached to the surface [12]. In this section of the paper we discuss the characterization of each modification step prior to our discussion of how different retinal analogs bind to the surface.…”
Section: Resultsmentioning
confidence: 99%